Experience of small tissue bites with conventional tissue bites in emergency setting for midline abdominal wound closure - Dogra, Varun; Sandhu, Silvi; Gilkar, Ishfaq Ahmad; Gupta, Shyam (International Surgery Journal, 2022)
Background: Midline incision provides excellent access to the abdominal cavity. However, wound infection following a laparotomy can increase morbidity as well as burden on health care system. Wound prognosis can be influenced by the type of incisions, suture material and the method of closure. This study aimed to assess the outcome of midline abdominal wound closure using two different techniques of wound closure. Methods: This was a prospective observational study and consisted of 300 consecutive patients ≥18 years of age undergoing abdominal surgery through a midline incision in emergency setting. Patients who were included in the study were then randomised into two groups. In group I, midline laparotomy was closed with large tissue bites and in group II small tissue bites were used. Results: Out of 300 patients included in this study, 150 patients were subjected to large tissue bites and another 150 patients to small tissue bites. 29 patients out of 150 patients (19%) in large tissue bites group and 16 patients (11%) in small tissue bites developed surgical site infection (SSI). 23 patients out of 50 patients (15%) in large tissue bites group and 11 patients (7%) in small tissue bites developed wound dehiscence. Conclusions: In this study, we found that the patients in group II whose midline laprotomy was closed with small tissue bites had better wound outcome postoperatively in terms of wound site infection and wound dehiscence.